Perancangan Website Gunung Hijau Lestari Menggunakan Metode Design Thinking - Natalia Siddharta; Delia Zahrani; Olivia Wijaya; Nazwa Munthaha Hendriyani Nasution; Taqiyya Safira Salsabilla; Anugerah Widi (Universitas Multi Data Palembang, 2026)
Gunung Hijau Lestari is one of the well-known swimming pool tourist destinations that is frequently visited by the public. This study aims to design an informational website for Gunung Hijau Lestari by applying the Design Thinking method to meet user needs and experiences. The design process begins with the empathize stage through direct on-site observation and the distribution of online questionnaires to visitors in order to identify their experiences, complaints, and expectations. The collected data are then analyzed as the basis for developing website features and content. The result of this study is a website design for Gunung Hijau Lestari that provides general information, facilities, services, ticket prices, and swimming pool conditions. This website is expected to help visitors access information more effectively and improve the quality of information services at the Gunung Hijau Lestari tourist site. The usability testing results showed an average SUS score of 82.4 and a task success rate of 94%, indicating that the proposed website design has excellent usability.